Are they protected? Immunity to vaccine‐preventable diseases in healthcare workers at an Australian hospital - Vivian Leung; Susan Harper; Monica Slavin; Karin Thursky; Leon Worth (Elsevier, 2014)
Abstract Objective: Australian guidelines for healthcare worker (HCW) vaccination were updated in 2010, and pre‐employment assessment of new employees has previously been identified as a priority. We determined the vaccination status of a cohort of existing HCWs at a tertiary hospital in Melbourne, Victoria. Methods: Random sampling of HCWs employed prior to 2006 with unknown/incomplete immunisation status was conducted between April and August 2011. Immunity to vaccine‐preventable diseases (VPDs) was determined serologically (hepatitis B, varicella, measles, mumps, rubella) and by questionnaire (diphtheria, tetanus and pertussis), with vaccination by a nurse immuniser. Results: Overall, 95 HCWs were evaluated. Mean age and duration of employment were 47.2 and 12.6 years, respectively. Forty‐seven staff (49%) required vaccination to comply with Australian immunisation guidelines: 18% were non‐immune to hepatitis B, 2% to varicella, 8% to measles, 19% to mumps and 13% to rubella. HCWs without serological hepatitis B immunity were all staff with clinical roles. Total costs were $7,527.34 (mean $222.79/HCW). Conclusions: Immunity to VPDs among existing HCWs was inadequate. About half assessed HCWs were non‐immune to at least one VPD, and non‐immunity to hepatitis B was high. A comprehensive assessment strategy for existing employees is required to enhance vaccination coverage and compliance with national guidelines. Implications: Adequately resourced 'look‐back' immunisation assessment programs are required to reduce the risks of VPDs among existing staff and patients. Review of current approaches and national consensus regarding the need for mandatory strategies would assist this process.